Addressing biodiversity knowledge shortfalls in New World Helicopsychidae (Insecta, Trichoptera): Potential distribution, environmental gradients, and identification of conservation and research priority areas - Rafael Pereira; Adolfo Calor (PLoS ONE, 2025)
This study provides an integrative analysis of Helicopsychidae biodiversity in the New World (NW), examining their distribution patterns, environmental gradients, biodiversity hotspots, and biodiversity knowledge shortfalls. We estimated species richness, delineated potential distribution, and identified areas of priority for research/conservation efforts. Our estimates indicate that up to 75% of NW Helicopsychidae species remain undescribed, with a notable Linnean shortfall at the subgenus level: approximately 50% of H. (Cochliopsyche) species and up to 77% of H. (Feropsyche) species are yet to be described. Knowledge of semaphoronts is also limited, with immature stages documented for only 15% of H. (Feropsyche) species and 6% of H. (Cochliopsyche). Distributional records are concentrated in the Brazilian subregion (between 0°–24°S), and most species have a short environmental distribution gradient. Based on currently known, priority conservation areas are in the Antilles and the Tropical Forest. For H. (Feropsyche), priority areas include low-altitude and coastal regions with low-order streams, whereas H. (Cochliopsyche) conservation priorities lie in the large river basins, especially in the Amazon and Atlantic Forests. Future research efforts should focus on H. (Feropsyche) in the Chaco and high-altitude areas of the Atlantic Forest, Cerrado, and Caatinga domains, as well as on H. (Cochliopsyche) across South America’s high order river (e.g., Amazon, Orinoco, Paraná, and São Francisco Rivers). Here, highlights recent advances in the taxonomy and distribution cataloguing of NW Helicopsychidae, despite significant progress, marjory of species remain undescribed, emphasizing the need for continued research. Although well-sampled regions like the Antilles, south Central America, Amazon coastal areas, and Central Atlantic Forest Ecological Corridor should be prioritized for conservation, vast areas such as the Amazon lowlands, northeast and southwest Atlantic Forest, and transition areas of Atlantic Forest and Dry Diagonal remain underexplored. To the best of our knowledge, this study represents one of first empirical analysis of environmental gradients for Trichoptera species. It establishes a foundation for understanding biogeographic patterns, environmental gradients, and the identification of biodiversity hotspots and potential distribution areas for Helicopsychidae in the New World. This work will guide future research and conservation efforts for Helicopsychidae and other Trichoptera groups in the region.